Concrete Strength Enhancement Due to External Steel Ring Confinement. (2017) - Safitri, Endah; Imran, Iswandi; Nuroji
Abstract: Designing sustainable concrete structures could be achieved by using less concrete material while maintaining required strength capacity. In order to meet the strength demand, the concrete element must use proper confinement. Confinement in concrete structures is required to enhance its ductility and load bearing capacity. Many investigations have been carried out to obtain constitutive equations for the confined concrete element of strength enhancement. The function of the equation is to predict the strength improvement and the confinement efficacy to provide lateral stress in resisting concrete deformation due to axial force. Internal confinement is commonly used in concrete elements. In this investigation, however, lateral confinement was achieved using an external steel ring. Rings of various widths were made by cutting a steel tube and installed on the concrete column at various distance intervals. These two variables: the ring width and distance between the rings were investigated to obtain correlation of volumetric ratio and lateral force produced by the rings. The constitutive equation of the externally confined column was derived as a function of effective lateral stress. This paper shows that the steel ring confined column strength was enhanced by factor of 2.29. Compared with the previous studies, the result of this investigation shows a coefficient of variation of 1–10%.